(untitled) (Research, Society and Development, 2024)
In recent years, kombucha has become quite popular, with a global market moving around 1.7 billion dollars in 2019 and with an expected annual growth of 20%. In this context, it is important to note that kombucha is quite important, suggesting better ways to reduce the risk of cardiovascular diseases, cancer, anxiety, depression, bacterial infections and diabetes. This study aims to evaluate the effect of kombucha consumption on blood glucose regulation, using an integrative literature review, with research in databases such as PubMed and ScienceDirect, selecting relevant articles through specific inclusion and exclusion criteria. We also analyzed studies that examined the glycemic effects of kombucha in experimental models, showing that regular consumption can reduce blood glucose and improve insulin sensitivity. The results will show that, due to bioactive composts, such as organic acids and polyphenols, kombucha has antioxidant and anti-hyperglycemic properties. In some studies, the effects are compared to years of antidiabetic medications. However, it is worth noting that it has long-term benefits for humans. In conclusion, research suggests that kombucha has potential as a functional food for glycemic control, providing more evidence that is necessary to consolidate its therapeutic efficacy.